2019
DOI: 10.7150/thno.36283
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane anchored photosensitive nano-device for lipid hydroperoxides burst and inducing ferroptosis to surmount therapy-resistant cancer

Abstract: Rationale: Ferroptosis is a regulated process of cell death caused by iron-dependent accumulation of lipid hydroperoxides (LPO). It is sensitive to epithelial-to-mesenchymal transition (EMT) cells, a well-known therapy-resistant state of cancer. Previous studies on nanomaterials did not investigate the immense value of ferroptosis therapy (FT) in epithelial cell carcinoma during EMT. Herein, we describe an EMT-specific nanodevice for a comprehensive FT strategy involving LPO burst.Methods: Mitochondrial membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 65 publications
1
89
0
Order By: Relevance
“…Due to iron's high reactivity, GSH oxidation induced by the metal should be considered a therapeutical approach and could be the main triggering factor leading to ferroptosis activation. Some reports have been published describing ferroptosis induction thought combination therapy where iron NPs are conjugated with ferroptosis inducers, such as the xc-cystine-glutamate exchanger's inhibitor Sorafenib, that induces glutathione depletion [240], as well as with drugs promoting lysosomes disruption [241,242]. NQO1 cannot compete with FSP1 in the reaction with hydrophilic peroxides, the situation is reversed when the substrate is lipid hydroperoxides.…”
Section: The Future Of Nanoparticles (Np) For Cancer Targeting and Timentioning
confidence: 99%
“…Due to iron's high reactivity, GSH oxidation induced by the metal should be considered a therapeutical approach and could be the main triggering factor leading to ferroptosis activation. Some reports have been published describing ferroptosis induction thought combination therapy where iron NPs are conjugated with ferroptosis inducers, such as the xc-cystine-glutamate exchanger's inhibitor Sorafenib, that induces glutathione depletion [240], as well as with drugs promoting lysosomes disruption [241,242]. NQO1 cannot compete with FSP1 in the reaction with hydrophilic peroxides, the situation is reversed when the substrate is lipid hydroperoxides.…”
Section: The Future Of Nanoparticles (Np) For Cancer Targeting and Timentioning
confidence: 99%
“…Recently, Sang and coworkers developed ferroptosis amplifier nanodevices for cancer treatment. Mitochondria targeted the nanophotosensitizer complex containing superparamagnetic IONPs (SPIONs), and when loaded with Sorafenib, exhibited antitumor activity by inducing ROS formation, lipid peroxidation, and ferroptosis of therapy resistant epithelial-to-mesenchymal transition cells [43]. The same group later described another mitochondrial membrane that targeted a photosensitive nanodevice.…”
Section: Ferroptosis As a Target For Oncotherapymentioning
confidence: 99%
“…Furthermore, SPION could elicit IL‐1βrelease and pyroptosis in macrophages, especially with the octapod and plate morphology 16 . Notably, it has been recently reported that sorafenib or cisplatin assembled into nano‐devices containing SPION, which are phagocytized by tumour cells and degraded into free divalent iron to accelerate Fenton reaction, leading to the lipid peroxidation burst to promote ferroptosis of tumour cells 17,18 …”
Section: Introductionmentioning
confidence: 99%